Steel-concrete composite bridges : designing with Eurocodes - Collings, David (ICE Publishing, 2013)
'Steel-Concrete Composite Bridges' is an essential guide to the latest methods in the design and construction of steel-concrete composite bridges. Containing precise data, in-depth examples and numerous illustrations, the second edition offers guidance from the first step in bridge design through to the construction process.
Keywords: Bridges -- Design and construction -- Standards.; Composite construction.; Eurocodes (Standards); elektronické knihy; electronic books